Prenatal Exposures Are Associated With Worse Neurodevelopmental Outcomes in Infants With Neonatal Opioid Withdrawal Syndrome - Benninger, Kristen L.; Borghese, Teresa; Kovalcik, Jason B.; Moore-Clingenpeel, Melissa; Isler, Cherie; Bonachea, Elizabeth M.; Stark, Ann R.; Patrick, Stephen W.; Maitre, Nathalie L. (Frontiers in Pediatrics, 2020)
Aim: To define a developmental trajectory in infants with neonatal opioid withdrawal syndrome (NOWS) and determine whether the impacted developmental domain varies with the type of antenatal exposure. Methods: We performed a retrospective cohort study of infants treated pharmacologically for NOWS and assessed using a standardized schedule for follow-up visits. We compared outcomes of the study population to published norms using one-sample t-tests. Multivariable models examined associations with exposures in addition to opioids. Results: In our cohort of 285 infants with 9–12-months testing, 164 (55.7%) were seen at 3–4 months, and 125 (44%), at 15–18 months. The majority (58%) had intrauterine drug exposures in addition to opioids. Neurodevelopmental scores of infants with NOWS at 3–4 and 9–12 months were not different from published norms. Cognitive and language scores at 15–18 months were worse than published norms. Male sex, older maternal age, and additional barbiturate or alcohol exposure were associated with worse outcomes. Conclusion: Infants with pharmacologically treated NOWS had development similar to unexposed infants during the 1st year but worse cognitive and language scores during the 2nd year. These data support the need for a prospective follow-up of large cohorts of infants with NOWS, with systematic assessments and an evaluation of contributing factors.